Expectant management of intrauterine growth restriction pregnancy: perinatal outcome - Andzane, Diana; Miskova, Anna; Polukarova, Svetlana; Gapatins, Igor (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Intrauterine growth restriction (IUGR) is the reason for increased morbidity and mortality in all periods of human life. The development of this pathology defines a variety of factors many of which are preventable. There is still no developed effective tactics for pregnancy and delivery, which would protect both mother and child from undesirable consequences. Methods: The research was made in Riga Maternity hospital in Latvia. In the research were included 96 neonates with the weight below 10th percentile (IUGR group) as well there was compiled the control group. We evaluated the condition of neonate by 13 criteria and studied its frequency depending on the gestational period. The weight of neonates was estimated using the percentile scales - intrauterine growth curves based on U.S. data. Results: In the subgroup of 37-39th week in the IUGR group in comparison with 40-42nd week subgroup, statistically more often was noticed hypoglycaemia, polycythaemia, acidosis, poor feeding, neurological abnormalities, transportation to an intensive care unit, transportation to another hospital for the further treatment and there was a higher number of days spent in the hospital. In the subgroup of 37-39th week in the control group were just 2 criteria that were statistically more frequent. Conclusions: Recognizing the IUGR to the fetus, there is justified the temporizing tactics with regard to resolution of pregnancy if only the health status of mother allows that and preeclampsia is excluded.